The book of brilliant bugs - French, Jess (DK Publishing, 2020)
Learn about the amazing world of insects and minibeasts in this gorgeously illustrated book of bugs. From the world's biggest beetle to dancing bees, you'll learn all about the incredible secret world of creepy crawlies. Did you know that ladybirds love to snuggle or how fireflies glow so brightly? Find out inside. The Brilliant Book of Bugs, written by insect expert Jess French and gorgeously illustrated by Claire McElfatrick, takes children on a fascinating journey of exploration, showing them just how amazing creepy-crawlies are, including insect relatives such as slimy slugs and scuttling centipedes. Discover how they pass on messages, how they compete for food, seek true love, and fill the air with buzzing wings.